The long-term impact of low-intensity surface fires on litter decomposition and enzyme activities in boreal coniferous forests - Koster, Kajar; Berninger, Frank; Heinonsalo, Jussi; Linden, Aki; Koster, Egle; Ilvesniemi, Hannu; Pumpanen, Jukka
In boreal forest ecosystems fire, fungi and bacteria, and their interactions, have a pronounced effect on soil carbon dynamics. In this study we measured enzymatic activities, litter decomposition rates, carbon stocks and fungal and microbial biomasses in a boreal subarctic coniferous forest on a four age classes of non-stand replacing fire chronosequence (2, 42, 60 and 152 years after the fire). The results show that microbial activity recovered slowly after fire and the decomposition of new litter was affected by the disturbance. The percent mass loss of Scots pine litter increased with time from the last fire. Slow litter decomposition during the first post-fire years accelerates soil organic matter accumulation that is essential for the recovery of soil biological activities. Fire reduced the enzymatic activity across all the enzyme types measured. Carbon-degrading, chitin-degrading and phosphorus-dissolving enzymes showed different responses with the time elapsed since the fire disturbance. Microbial and enzymatic activity took decades before recovering to the levels observed in old forest stands. Our study demonstrates that slower post-fire litter decomposition has a pronounced impact on the recovery of soil organic matter following forest fires in northern boreal coniferous forests. 2016